2019
DOI: 10.3390/cells8121597
|View full text |Cite
|
Sign up to set email alerts
|

The Upstream Pathway of mTOR-Mediated Autophagy in Liver Diseases

Abstract: Autophagy, originally found in liver experiments, is a cellular process that degrades damaged organelle or protein aggregation. This process frees cells from various stress states is a cell survival mechanism under stress stimulation. It is now known that dysregulation of autophagy can cause many liver diseases. Therefore, how to properly regulate autophagy is the key to the treatment of liver injury. mechanistic target of rapamycin (mTOR)is the core hub regulating autophagy, which is subject to different upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(127 citation statements)
references
References 299 publications
(409 reference statements)
6
113
0
Order By: Relevance
“…Mammalian mTOR is a component of mechanistic target of rapamycin c1 (mTORc1). When it is sensitive to rapamycin, it regulates intracellular nutrition, growth factors, pressure and other signals and activates PRAS40, a protein that binds to mTORc1, causing PRAS40 to separate from mTORc1 (22). When it is not sensitive to rapamycin, it controls cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian mTOR is a component of mechanistic target of rapamycin c1 (mTORc1). When it is sensitive to rapamycin, it regulates intracellular nutrition, growth factors, pressure and other signals and activates PRAS40, a protein that binds to mTORc1, causing PRAS40 to separate from mTORc1 (22). When it is not sensitive to rapamycin, it controls cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Latest Studies manifested that it can promote liver fibrosis by activating PI3K/AKT/mTOR signaling. [47,48] However,the effect and relationship of PPAR-γ and PI3K/AKT/mTOR signaling pathway in Cholestatic Liver disease is not certain. Through our research we found cholestatic liver can significantly elevate the P-Akt P-mTOR protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…7 The mTOR plays a negative role in autophagy by regulating autophagy-related proteins and lysosome biosynthesis. 8 The author proposes selective interference of mTORC1 (mTOR complex 1)/RAPTOR (regulatoryassociated protein of mTOR) to protect disc cells from inflammation-induced apoptosis, senescence, and prevent ECM catabolism.…”
Section: Moving Forward: Gene Therapy For Intervertebral Disc Degenermentioning
confidence: 99%